Pharmaceutical Care dan Kepatuhan Minum Obat Hipertensi Terhadap Lansia Dengan Hipertensi - Ayu Wandira; Cindiansya Cindiansya; Jihan Rosmayati; Riswanti Frida Anandari; Sri Anbar Naurah; Maya Arfania; Dedy Frianto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Elderly people (elderly) refer to people aged 60 years or more. Elderly people (elderly) are at high risk for various degenerative diseases that usually show no symptoms when they are young, namely hypertension. Hypertension is called the "silent killer" because it occurs without symptoms or warning signs which many people ignore when they are young. The reason for the delay in treating hypertension patients is that the majority of patients go to medical institutions if complications occur and the lack of awareness of medication adherence causes cases of disease to get out of control. especially in elderly people (Elderly). Therefore, pharmacists can play an active role in the management of hypertension therapy through Pharmaceutical Care services with assessment steps, preparing treatment plans, implementation, and monitoring. Pharmaceutical Care is a patient-oriented pharmaceutical service, where pharmacists contribute to other health workers to increase knowledge, and adherence, and improve the quality of life for patients with hypertension, especially the elderly. The data used in writing this article review was collected using the literature study method. Library searches were carried out using online-based library search instruments such as 3 sources, namely Google Scholar, PubMed, and Science Direct. The journals taken in this study consisted of 13 international journals and 2 national journals with a range of years (2013-2023).